Optical Analysis of Dry Reforming of Methane in Microwave-Induced Plasma at Atmospheric Pressure - Xiuqiang Zhang; Nobusuke Kobayashi; Yoshinori Itaya (Journal of Chemical Engineering of Japan)
Spectroscopic analysis was conducted on microwave (MW) argon (Ar) plasma, promoted by a charcoal bed, during the dry reforming of methane at atmospheric pressure. High-resolution spectroscopic analysis revealed five prominent peaks near the CH (B2Σ− → X2П) region when methane dissociation occurred in Ar plasma. The most prominent peak corresponded to the energy excitation of Ar (II) ions at 388.03 nm, and the atomic transition process was 3s23p4(3P)4d4D1/2 → 3s23p4(3P)4p4D°1/2. This process might be enhanced by interactions with intermediates or free radicals produced during the methane dissociation reaction. The ion temperature of the Ar (II) in MW plasma was calculated from the intensity of any two of the five characteristic peaks. Due to different transition processes, the temperature of ions also exhibited significant variation, consistent with the characteristics of a non-equilibrium plasma. The Ar (II) ion temperature reached as high as 18,000 K. According to the Boltzmann plot, the relative error of the ion temperature in this study was less than 0.02 when the ion temperature was lower than 10,000 K, and the error corresponding to the highest ion temperature was also less than 0.05, indicating that the temperature of the Ar (II) ion describing a particular energy state can be determined with reasonable accuracy. Furthermore, activated Ar (II) ions inducing methane dissociation through collisions are considered to be the primary cause of methane dissociation.